Skill based immigrant selection and labor market outcomes by visa category - Abdurrahman Aydemir (Institute for the Study of Labor (IZA), 2012)
Attracting skilled immigrants is emerging as an important policy goal for immigrant receiving countries. This article first discusses the economic rationale for immigrant selection. Selection mechanisms of receiving countries are reviewed in the context of deteriorating labor market outcomes for immigrants across destination countries which fuels the debate on selection. Next, the variation in immigrant characteristics across countries and visa types is discussed. The article then reviews the evidence on labor market outcomes of immigrants by visa category that portrays the experiences of countries with different selection mechanisms and underlines the challenges for realizing aimed benefits of a skill based immigrant selection policy.
urn:nbn:de:101:1-201207125660
Keywords: J61; J68; 330; immigration; selection; immigration policy; visa category; point system; Migrationspolitik; Einwanderungsrecht; Qualifikation; Hochqualifizierte Arbeitskräfte; Wirkungsanalyse; Migranten; Erwerbsverlauf; Welt